2014
DOI: 10.1111/jmwh.12111
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Video Show for Community Behavior Change on Maternal and Newborn Health in Rural Ethiopia

Abstract: Introduction: A number of factors affect Ethiopia's efforts to meet Millennium Development Goals 4 and 5 to reduce maternal and newborn mortality. The Maternal and Newborn Health in Ethiopia Partnership (MaNHEP) project, as part of its overall strategy, implemented behavior change communication interventions to increase women's demand for and use of antenatal, birth, and postnatal services. Seeking to reach "mediadark" areas, MaNHEP implemented a mobile video show focused on maternal and newborn health. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…mHealth via text messaging has also been a means of delivering health information and direct health services [ 10 ]. Recent evaluations of mHealth programs have demonstrated that various forms of text messaging can increase the utilization of antenatal care, skilled birth attendance and postnatal health services while improving customer satisfaction [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…mHealth via text messaging has also been a means of delivering health information and direct health services [ 10 ]. Recent evaluations of mHealth programs have demonstrated that various forms of text messaging can increase the utilization of antenatal care, skilled birth attendance and postnatal health services while improving customer satisfaction [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We describe the extent to which the project's objectives were met and highlight implications for policy, programming, and research. Other articles in this supplement issue of the Journal of Midwifery & Women's Health provide more detailed descriptions and results of MaNHEP interventions …”
Section: Introductionmentioning
confidence: 99%
“…This integration was associated over a 2‐year period, with increased completeness of care, increased use of skilled providers and health extension workers at birth, and a 10‐fold increase in postnatal care coverage. Desta et al describe how this integrated effort was reinforced by a novel mobile van video show, among other behavior change communications activities.…”
Section: Articles In This Special Issuementioning
confidence: 99%